Fabrication of Catalyst Coated Membranes by Ultrasonic Spray for Proton Exchange Membrane Water Electrolysers - Mawungwe, Nyasha (Department of Chemical Engineering, 2024)
Renewable hydrogen, referred to as green hydrogen (GH), holds significant importance in the endeavour to decarbonise the transportation and industrial sectors. GH is generated via the electrochemical process of water splitting, utilising excess renewable energy sources such as solar and wind, thus serving as a sustainable means of energy storage. The production of GH can be done in a proton exchange membrane water electrolyser (PEMWE), by splitting water into hydrogen and oxygen utilising an important component called the catalyst-coated membrane (CCM). The CCM is composed of a membrane coated with noble metal-based catalyst nanoparticles that make up the anode and cathode electrodes. The sluggish anode kinetics and the elevated cost associated with the CCM have acted as barriers to the widespread acceptance of PEMWEs. In this study, we used ultrasonic spraying for catalyst coating. Previous research suggests that optimising these parameters can enhance PEMWE performance and commercial viability. The research conducted involved an ultrasonic spraying parameter variation and an anode catalyst loading study. The ultrasonic spraying variation investigated the nozzle height and nozzle speed. The anode catalyst ink was formulated from a commercial catalyst and applied to each membrane forming a half CCM, and thereafter, combined with a commercially developed cathode to form a full CCM. The CCMs were physically characterised, and electrochemically tested. The results were compared to assess the impact of ultrasonic spraying parameters and anode loading on performance and catalyst utilisation. The fabricated samples with approximately 2 mg Ir anode loading were further compared to a commercial CCM benchmark, considering the CL surface, microstructure, performance, and catalyst utilisation. The results showed the influence of spraying parameters, catalyst type, and loading on microstructure, performance, and utilisation. This showed the importance of optimising parameters and loading to develop comparable low-loaded catalyst layers to assist PEMWE adoption.